Analisis Tingkat Kepuasan Masyarakat Terhadap Pelayanan Kesehatan di Poliklinik Rumah Sakit Umum Daerah Kota Kayuagung - Eliya, Eliya; Noviadi, Fitri; Kusumawaty, Ira (JURNAL KESEHATAN TERAPAN, 2025)
Patient satisfaction is one of the important indicators that must be considered in health services. The definition of patient satisfaction according to Kotler is a person's feeling of pleasure or disappointment that arises after comparing their perception or impression of the performance or results of a product and their expectations. The standard of patient satisfaction in health services is set nationally by the Indonesian Ministry. The purpose of this study was to determine the relationship between tangible evidence, responsiveness, reliability, assurance, and empathy and several factors that influence community satisfaction at the Kayuagung City Regional General Hospital Polyclinic. The design of this study is an analytical survey with a cross-sectional study approach. The population is all outpatients at the Kayuagung City Regional Hospital Polyclinic which is calculated based on the number of patients in 2025 of 24,709 with a sample size of 100 respondents. The statistical analysis used is univariate, bivariate, and multivariate analysis to see the relationship between factors that affect health services, age, gender, education, employment status, economic status, payment method, polyclinic visited, patient status, disease suffered and distance / access with the dependent variable of the level of community satisfaction at the Outpatient Polyclinic of Kayuagung City Hospital. From the entire analysis process that has been carried out, it can be concluded that of the ten independent variables, there are variables that are related and there are variables that are not related simultaneously to the level of community satisfaction at the Outpatient Polyclinic of Kayuagung City Hospital.